2022
DOI: 10.52547/aassjournal.1079
|View full text |Cite
|
Sign up to set email alerts
|

Causal Factors Related to Management of eSport Clubs in Thailand

Abstract: Background. Currently, the Public and private sectors are working to accelerate eSports into the path of creating income for athletes and young people. The Ministry of Health has disclosed that the number of games increased more than doubled back. eSports is widespread in Thailand. Although eSports are more popular among Thai teenagers, they face financial problems in management. The paper is more innovative than other research because there is so much eSport research in Thailand, but none is used to study thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It led to the need for transformations in the sports management system and consideration of new determinants of its development. In particular, Pumsanguan and Thithathan (2022) found that the most significant factors that determine the features of eSports management are the activities of government organizations, the level of development of society and culture, the competitiveness of eSports, the state of infrastructure, the variety of types of games, the development of the private sector and technological development. Recently, the study of the connection between sports development and health care has been gaining relevance.…”
mentioning
confidence: 99%
“…It led to the need for transformations in the sports management system and consideration of new determinants of its development. In particular, Pumsanguan and Thithathan (2022) found that the most significant factors that determine the features of eSports management are the activities of government organizations, the level of development of society and culture, the competitiveness of eSports, the state of infrastructure, the variety of types of games, the development of the private sector and technological development. Recently, the study of the connection between sports development and health care has been gaining relevance.…”
mentioning
confidence: 99%